An Investigation on the Top-of-the-line Corrosion Using Novel Methods - Islam, Md Mayeedul (Curtin University, 2017)
Top-of-the-line corrosion (TLC) occurring at the inner wall of wet gas transportation pipelines due to the condensation of water vapour is one of the major concerns in the oil and gas industry. Primary challenges associated with TLC are relevant to its control and monitoring. Therefore, the research presented in this thesis involved the design and development of electrochemical monitoring techniques for TLC for the first time and investigating the mechanism of TLC by revisiting the influences of different parameters.